(untitled) (Damascus University Journal of Historical Studies, 2025)
Cleanliness is one of the most important elements of human existence, and the inhabitants of cities cannot continue to live in health and safety unless they maintain its cleanliness. In the subject of the study, “Cleanliness in the city of Damascus in the Ottoman era,” we asked: Who was doing the cleaning work in it? One side or several? It is necessary to study the hygiene factors in the city such as the availability of water, social culture and the role of the Ottoman authority, as well as cleanliness in homes and markets, and study its obstacles and difficulties, leading to the paid cleaning services that have come to refer to civilizational development and address the issue of cleanliness from a perspective more necessary, Cleanliness has changed from a secondary matter to a major thing for which money is paid, and to address all of the aforementioned, we returned to the authentic historical sources, most notably the records of the Sharia courts in Damascus and the books of travelers in the absence of previous studies on the subject.